Effects of androgen on extracellular vesicles from endothelial cells in rat penile corpus cavernosum. (9th February 2021) - Yan, Ling‐Tao; Yang, Zhi‐Hui; Lin, Haocheng; Jiang, Jun; Jiang, Rui
Abstract: Background: The explicit mechanism of erectile dysfunction caused by low androgen status is unknown. It was reported that eNOS was expressed in extracellular vesicles (EVs). Androgen may regulate erectile function by affect the release of EVs from endothelial cells. Objectives: To investigate whether androgen affects the production of EVs and nitric oxide (NO) in endothelial cells of rat penile corpus cavernosum. Materials and Methods: Endothelial cells of rat penile corpus cavernosum were isolated and purified from 6‐week‐old healthy male Sprague Dawley (SD) rats. Endothelial cells were treated with different concentrations of dihydrotestosterone (DHT) in a cell culture medium as follows: no‐androgen group (NA group, DHT 0 nmol/L), very‐low androgen group (VLA group, DHT 0.1 nmol/L), low androgen group (LA group, DHT 1 nmol/L), and physiological concentrations androgen group (PA group, DHT 10 nmol/L). After 24 h, EVs of supernatant in each group were isolated and identified. The content of EVs and NO in the supernatant and the expression of CD9, CD63, TSG101, and eNOS in EVs were detected. Results: Positive expression of CD9, CD63, TSG101, and eNOS was found in isolated EVs. The concentration of EVs was lower in the NA group compared with other groups ( p  < 0.01). The expression of eNOS and the concentration of NO was lower in the NA group than that in other groups ( p  < 0.05); it was lower in the VLA group than that in the LA group ( p  < 0.05) and lower in LA group than that in PA group ( p  < 0.05). When the concentration of DHT in endothelial cell culture medium ranged from 0 to 10 nmol/L, the concentration of DHT was positively correlated with the content of EVs and NO. Conclusion: Decrease in eNOS‐expressing EVs is one mechanism of NO reduction in endothelial cells of rat corpus cavernosum caused by low androgen levels.